Bibliometric Analysis on Digital Leadership in the Hotel Industry and Future Trends (Architecture Image Studies, 2025)
Purpose – This bibliometric review critically synthesizes the existing research on digital leadership within the context of the hotel industry's digital transformation (DT). In response to a growing body of fragmented literature, this study employs bibliometric techniques to analyze the literature on digital leadership in the hotel sector. The aim is to identify key contributors and delineate core thematic clusters related to digital leadership. Design/Methodology – In analysing the significant and multifaceted topic of digital leadership, this study investigates the subject within the context of the hospitality industry, with a particular focus on environmental issues. The research evaluates themes based on past, present, and future trends in digital leadership in hotels, utilizing a bibliographic database sourced from the Web of Science (WoS). Findings – Several themes were identified from the role of digital transformation and impact on the hotel industry. The main themes include three aspects-“the concepts and elements of the digital leadership in the hotel industry”, “the structure of digital leadership in the hotel industry” and “the future trends of digital leadership in the hotel industry” through VOS viewer analysis.